2012
DOI: 10.1007/s10705-012-9504-2
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia volatilization from nitrogen fertilizers applied to cereals in two cropping areas of southern Australia

Abstract: As farmers in southern Australia typically apply nitrogen (N) to cereal crops by top-dressing with ammonia (NH 3 ) based fertilizer in late winter or early spring there is the potential for large losses of NH 3 . This paper describes the results of micrometeorological measurements to determine NH 3 loss and emission factors following applications of urea, urea ammonium nitrate (UAN), and ammonium sulfate (AS) at different rates to cereal crops at two locations in southern Australia. The amounts of NH 3 lost ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 32 publications
1
30
1
Order By: Relevance
“…Rapid dissolution of granules and urea release into the soil solution is followed by urea hydrolysis and subsequent NH 4 + formation, a process that consumes hydrogen protons . Given the instability of NH 4 + in alkaline conditions, it is converted to NH 3 , which is lost in gas form . Therefore, NH 3(g) ‐N losses are more pronounced in fast‐release fertilizers, such as G1, compared to G2 and G3 (Fig.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Rapid dissolution of granules and urea release into the soil solution is followed by urea hydrolysis and subsequent NH 4 + formation, a process that consumes hydrogen protons . Given the instability of NH 4 + in alkaline conditions, it is converted to NH 3 , which is lost in gas form . Therefore, NH 3(g) ‐N losses are more pronounced in fast‐release fertilizers, such as G1, compared to G2 and G3 (Fig.…”
Section: Discussioncontrasting
confidence: 59%
“…6,7 Given the instability of NH 4 + in alkaline conditions, it is converted to NH 3 , which is lost in gas form. 21,22 Therefore, NH 3(g) -N losses are more pronounced in fast-release fertilizers, such as G1, compared to G2 and G3 (Fig. 3).…”
Section: Discussionmentioning
confidence: 97%
“…In an irrigated common-bean crop system in the Brazilian Cerrado, with broadcasted urea, Cruvinel et al (2011) found an emission factor for N 2 O-N of 0.20%. The emission of N 2 O-N found in the present study was equivalent to that measured by Metay et al (2007) Turner et al (2012) found NH 3 -N losses ranging from 1.8 to 23% of the added N fertilizers in different cropping systems. They attributed the variability of these results to soil-climate conditions, such as soil moisture, temperatures, and wind speed.…”
Section: Resultssupporting
confidence: 78%
“…With an extremely low EF (0.05%) for N 2 O in this dry environment (Table 4), the majority of the gaseous loss was probably from NH 3 and N 2 loss. Volatilisation of NH 3 could be significant (Freney et al 1983;Turner et al 2012) as N was top-dressed and no significant rainfall fell until 5 days after N was applied (17 mm, Fig. 1).…”
Section: Discussionmentioning
confidence: 99%